Esperança e medo: o movimento das paixões no discurso político - Cavalcante, Marcelo Cesar (2009)
This research aims to analyze how fear end hope as passions are used in the political discourse during campaign. Specifically, it seeks to show that the audience is a mere rhetorical resource built by the speaker. Thus, we defend that the ethos, pathos and logos are in constant interaction towards the act of persuasion. Knowing the needs and desires of the audience, the speaker works with feelings related to absence, lack, frustration of the basic human needs. After denouncing a chaotic situation of disorder provoking fear and despair, the speaker announces himself as the savior, as the only way to rescue an era of order, justice and security. The moment of the promise of the action and the action itself causes the feeling of hope of a better life embodied by the politician considered a public man. At this moment we have a new semantic feature which stems from the foundation on the Carta de Pero Vaz de Caminha, who once wrote and the best seed is to save these people , creating the myth of the politician as the savior, the hero. Without putting an end on this issue, this work leaves a reflection whether the passions of fear and hope are common to any political discourse during electoral campaign